Crop diversification in black pepper gardens with tuber and fodder crops - Thankamani, C.K.; Kandiannan, K.; Madan, M.S.; Raju, V.K.; Hamza, S.; Krishnamurthy, K.S. (Journal of Plantation Crops, 2011)
With an objective to augment the income from black pepper plantation by intercropping tuber and fodder crops, a field experiment was conducted in RBD at Ambalavayal (Kerala) for two years 2007 to 2009. Based on yield performance , tuber crops such as cassava, elephant foot yam , coleus, and spices like ginger and turmeric, and fodder crops viz. hybrid napier grass, guinea grass, congo signal grass were selected as treatments apart from a control (sole crop of black pepper). The results indicated that higher black pepper yield was obtained under intercropping situation compared to sole crop. The maximum black pepper equivalent yield (1,147 kg/ha) was recorded by elephant foot yam followed by ginger (956 kg/ha). In the case of fodder crops, maximum pepper equivalent yield was recorded by hybrid napier grass Co 3 (2,633 kg/ha) followed by guinea grass (2,347 kg/ha). Maximum net return of ` 2, 70, 230/ ha was obtained from black pepper + elephant foot yam followed by black pepper + ginger (` 2, 60,657/ ha). Among the fodder crops, hybrid napier grass recorded maximum net return (` 2, 05,950/ ha) followed by guinea grass. Benefit: cost ratio was higher for inter cropping hybrid napier grass (3.7) followed by ginger (3.5) and elephant foot yam (3.4) in black pepper gardens.